Towards a Whole-Person Translator Education Approach in Translation Teaching on University Degree Programmes - Tan, Zaixi (Meta, 2008)
AbstractThis article posits that translation teaching in degree programmes in translation at the tertiary level is not mere translator training. Rather, it is both training and education, and very often more education than training. On this proposition, it emphasizes the need for such programmes to take into full consideration the holistic development of the students in their education as translator/translation specialist. Most essential to the model that the paper proposes to develop are its two componential concepts, namely the “whole-person translator education” concept and the “translator-development pyramid” concept. Both of these concepts, together with issues on the various kinds of translation competences that are integrated to create a ‘whole person’ in the translation student, are analysed and discussed in depth, in order to shed light on the development of what could be seen as an innovative pedagogical model for translation teaching in university degree programmes in translation.